2016
DOI: 10.1097/cin.0000000000000200
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Simulation-Problem–Based Learning for Sex Education

Abstract: Nurses often encounter clients with sexual problems. A sexual problem is complicated and affects the quality of the client's life, and proper care requires the nurse to understand a variety of sex-related issues. Therefore, effective sex education for nursing students is necessary to prepare them for potential challenges from the client's sexual problems. In this study, we developed a simulation-problem-based sex education program for nursing students. The program immerses the students in a sex-related clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
1
8
1
2
Order By: Relevance
“…13,14,18,21 Additionally, the sexual healthcare education, based on the age-specific approach with evidence-based practice in the nursing curriculum, was determined to improve the self-efficacy of nursing students in providing counseling according to the patient's sexual healthcare needs. 3,[28][29][30] However, the total SABS score difference between third and fourth-year nursing students was not significant and the mean SABS score of the fourth-year nursing students tended to increase in this study. Such theoretical and clinical practice do not have a permanent effect on nursing students' attitudes and beliefs toward sexual healthcare.…”
Section: Discussionmentioning
confidence: 70%
“…13,14,18,21 Additionally, the sexual healthcare education, based on the age-specific approach with evidence-based practice in the nursing curriculum, was determined to improve the self-efficacy of nursing students in providing counseling according to the patient's sexual healthcare needs. 3,[28][29][30] However, the total SABS score difference between third and fourth-year nursing students was not significant and the mean SABS score of the fourth-year nursing students tended to increase in this study. Such theoretical and clinical practice do not have a permanent effect on nursing students' attitudes and beliefs toward sexual healthcare.…”
Section: Discussionmentioning
confidence: 70%
“…Twenty‐two RCTs involving 1969 participants were included (Bai et al, 2017; Bukumiric et al, 2022; Cong et al, 2017; Dyke et al, 2001; Faisal et al, 2016; Jamshidi et al, 2021; Khatiban et al, 2019; Khatiban & Sangestani, 2014; Kim, 2019; Kim & Shin, 2014, 2016; Lee & Son, 2022; Li et al, 2020; Lian & He, 2013; Lin et al, 2010; Lohse et al, 2003; Peng et al, 2021; Pourshanazari et al, 2013; Smits et al, 2003; Sun & Qi, 2017; Wu et al, 2020; Zhao & Cong, 2019). The numbers of participants in the experimental and control groups were 1003 and 966, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The knowledge outcomes were derived mainly from theoretical examinations. Fifteen studies reported this type of outcome, among which 11 reported post-interventional examination results about knowledge (Bai et al, 2017;Bukumiric et al, 2022;Cong et al, 2017;Dyke et al, 2001;Faisal et al, 2016;Kim & Shin, 2014;Li et al, 2020;Lian & He, 2013;Lohse et al, 2003;Peng et al, 2021;Pourshanazari et al, 2013), three reported both pre-and post-intervention examination results (Jamshidi et al, 2021;Kim & Shin, 2016;Smits et al, 2003), and one reported the change of examination results after interventions (Khatiban & Sangestani, 2014; Table 2). The max- Most of the performance outcomes were objective assessments from tutors or supervisors.…”
Section: Knowledge Performance and Satisfaction Outcomesmentioning
confidence: 99%
“…In scenarios in which the 2 strategies were used together, but without addressing the issue of sexuality, students reported that the activity favored knowledge acquisition. [12][13][14] With the identified gaps, promotion of SCI sexual health includes working with nursing students on the interrelated domains of knowledge, attitude, and self-efficacy. A positive attitude and increased confidence to address an issue require first an improvement of the knowledge related to it.…”
mentioning
confidence: 99%
“…Previous research that used these strategies separately to address sexuality has pointed to its positive effect on knowledge, attitudes, and self-confidence. In scenarios in which the 2 strategies were used together, but without addressing the issue of sexuality, students reported that the activity favored knowledge acquisition 12–14…”
mentioning
confidence: 99%